Inflammatory Cells Accelerated Carotid Artery Calcification via MMP9: Evidences From Single-Cell Analysis - Liang, Xiaobing; He, Wanbing; Zhang, Hua; Luo, Dongling; Zhang, Zhengzhipeng; Liu, Aiting; Wang, Jinkai; Huang, Hui (Frontiers in Cardiovascular Medicine, 2021)
Vascular calcification (VC) is an important predictor of prognosis in atherosclerosis. To investigate the transformation of vascular smooth muscle cells (VSMCs) in the pre-calcification period, we analysed single-cell sequencing data from carotid artery calcified core and paracellular tissue then successfully identified a subpopulation of inflammatory macrophage-like VSMCs. Based on the results of enrichment analysis and protein-protein interaction analysis, we identified MMP9 as an important factor in the phenotypic transformation of VSMCs. Tracing upstream transcription factors revealed that RELA regulates the expression of MMP9. Knockout of RELA attenuated MMP9 expression, reduced the expression of BMP2 and the macrophage marker LGALS3 in vascular smooth muscle in an inflammatory state. The level of MMP9 in serum was significantly correlated with the inflammatory response. This study reveals that the phenotypic transformation of VSMCs can be regulated by modulating MMP9, providing a new idea for the early treatment of VC.